Analysis of Accident Rate in Kolonel Sugiono Street, Malang City: Analisis Tingkat Kecelakaan di Jalan Kolonel Sugiono Kota Malang - Rifky Aldila Primasworo; M. Sa’dillah; Maria Goreti Ganjom (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
Kolonel Sugiono street is included in the administrative area of ​​Mergosono Sub-Village, Kedungkandang District, Malang City and is a connecting route between Malang Regency and Malang City. In addition, it is also one of the routes that connects Malang City and Surabaya City, with the road function being a Secondary artery and a national road. Kolonel Sugiono street is one of the lanes with a quite high flow of vehicles every day. Kolonel Sugiono street is an area that has quite a lot of blackspot due to the frequent occurrence of traffic accidents. Based on Malang City Traffic data, there were 51 accidents occurred in 2014-2016 and 40 accidents in 2017-2021, both on Kolonel Sugiono street. This study aimed to determine the traffic’s characteristics, identify blacksites and blackspots, as well as solutions and efforts to improve road safety. According to the analysis results, the service level of Kolonel Sugiono street is 0.98 that is categorized as criterion E, namely the traffic volume is approaching or at its capacity, the flow is unstable with frequently stop conditions. Furthermore, based on the Z-Score and Cusum analysis, Kolonel Sugiono road is identified as a Blacksite and Blackspot because it has a positive Z-Score value, namely segment I is 3.1 and in segment II is 5, has a Cusum value, namely in segment 1 is 32 and in segment II has a value of 28.2. Solutions and efforts to improve road safety are paying attention to, repairing, and installing traffic signs, traffic signaling devices, and other road complementary factors.